Have clinicians adopted the use of brain MRI for patients with TIA and minor stroke?. (17th January 2017) - Chaturvedi, Seemant; Ofner, Susan; Baye, Fitsum; Myers, Laura J.; Phipps, Mike; Sico, Jason J.; Damush, Teresa; Miech, Edward; Reeves, Mat; Johanning, Jason; Williams, Linda S.; Arling, Greg; et al.
Abstract : Background: Use of MRI with diffusion-weighted imaging (DWI) can identify infarcts in 30%–50% of patients with TIA. Previous guidelines have indicated that MRI-DWI is the preferred imaging modality for patients with TIA. We assessed the frequency of MRI utilization and predictors of MRI performance. Methods: A review of TIA and minor stroke patients evaluated at Veterans Affairs hospitals was conducted with regard to medical history, use of diagnostic imaging within 2 days of presentation, and in-hospital care variables. Chart abstraction was performed in a subset of hospitals to assess clinical variables not available in the administrative data. Results: A total of 7, 889 patients with TIA/minor stroke were included. Overall, 6, 694 patients (84.9%) had CT or MRI, with 3, 396/6, 694 (50.7%) having MRI. Variables that were associated with increased odds of CT performance were age >80 years, prior stroke, history of atrial fibrillation, heart failure, coronary artery disease, anxiety, and low hospital complexity, while blood pressure >140/90 mm Hg and high hospital complexity were associated with increased likelihood of MRI. Diplopia (87% had MRI, p = 0.03), neurologic consultation on the day of presentation (73% had MRI, p < 0.0001), and symptom duration of >6 hours (74% had MRI, p = 0.0009) were associated with MRI performance. Conclusions: Within a national health system, about 40% of patients with TIA/minor stroke had MRI performed within 2 days. Performance of MRI appeared to be influenced by several patient and facility-level variables, suggesting that there has been partial acceptance of the previous guideline that endorsed MRI for patients with TIA.